Targeting IgE Antibodies by Immunoadsorption in Atopic Dermatitis - Kasperkiewicz, Michael; Schmidt, Enno; Ludwig, Ralf J.; Zillikens, Detlef (Frontiers in Immunology, 2018)
One major hallmark of atopic dermatitis (AD) is the elevated level of total serum IgE, which has been reported to be partly of the autoreactive type in a subset of patients. Immunoadsorption (IA) has been successfully applied in a variety of classical autoantibody-mediated diseases such as pemphigus. Recent reports proposed the use of IA also for patients with severe AD and high total serum IgE levels. In this mini-review, we summarize the current knowledge about this novel treatment approach for AD and briefly discuss the so far incompletely known role of autoreactive IgE as potential target of IA therapy in this common inflammatory skin disorder.